The impact of disseminating the whole-community project '10,000 Steps': a RE-AIM analysis - Van Acker, Ragnar (BioMed Central, 2011)
BACKGROUND: There are insufficient research reports on the wide-scale dissemination of effective whole-community physical activity (PA) programs. The purpose of this paper is to evaluate the impact of the wide-scale dissemination of '10,000 Steps', using the RE-AIM framework. METHODS: Dissemination efforts targeted a large region of Belgium and were concentrated on media strategies and peer networks of specific professional organizations, such as local health promotion services. Heads of department of 69 organizations received an on-line survey to assess project awareness, adoption, implementation and intended continuation of '10,000 Steps'. On the individual level, 755 citizens living in the work area of the organizations were interviewed for project awareness and PA levels. Measures were structured according to the RE-AIM dimensions (reach, effectiveness, adoption, implementation, maintenance). Independent sample t and chi-square tests were used to compare groups for representativeness at the organizational and individual level, and for individual PA differences. RESULTS: Of all organizations, 90% was aware of '10,000 Steps' (effectiveness - organizational level) and 36% adopted the project (adoption). The global implementation score was 52%. One third intended to continue the project in the future (maintenance) and 48% was still undecided. On the individual level, 35% of citizens were aware of '10,000 Steps' (reach). They reported significantly higher leisure-time PA levels than those not aware of '10,000 Steps' (256 ± 237 and 207 ± 216 min/week, respectively; t = -2.8; p < .005) (effectiveness - individual level). When considering representativeness, adoption of '10.000 Steps' was independent of most organizational characteristics, except for years of experience in PA promotion (7.6 ± 4.6 and 2.9 ± 5.9 years for project staff and non-project staff members, respectively; t = 2.79; p < 0.01). Project awareness in citizens was independent of all demographic characteristics. CONCLUSIONS: '10,000 Steps' shows potential for wide-scale dissemination but a supportive linkage system seems recommended to encourage adoption levels and high quality implementation.